Herbaceous seeds dominates the soil seed bank after long-term prescribed fire, grazing and selective tree cutting in savanna-woodlands of West Africa - Zida, D.; Sanou, L.; Diawara, S.; Savadogo, P.; Thiombiano, A. (Elsevier, 2020)
The soil seed bank (SSB) is an important source of resilience for plant communities subjected to disturbances. This study aimed to identify characteristics of the SSB, its relationship with aboveground vegetation (AGV), and its significance for restoration of vegetation in West African savanna-woodlands. Data were collected from two long-term factorial experiments established in 1992 in Burkina Faso to examine the long-term ecological effects of grazing, early fire, selective tree cutting on savanna-woodland ecosystem. A total of 1920 soil samples were taken from three soil layers (i.e. 0-3 cm, 3–6 cm and 6–9 cm) and the SSB was assessed using the seedling emergence technique. The emerged seedlings were dominated by non-woody taxa. Only two woody species that were Flueggea virosa and Mitragyna inermis emerged, showing that woody species feature little in the SSB. The SSB density and richness decreased significantly with soil depth. Non-metric multidimensional scaling (NMDS) ordination indicated a lack of correspondence between the AGV and SSB. The results suggest site-specific responses to disturbance also following long-term disturbance, the SSB will be ineffective in regenerating the remnant vegetation of West African savanna-woodlands. Hence, ensuring the resilience of West African savanna woodland ecosystems will require targeted introductions (i.e. planting and seeding) of indigenous species and a reduction in on-going disturbances.